2003
DOI: 10.1016/s0168-1605(02)00192-7
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of uncertainty and variability in bacterial growth using Bayesian inference. Application to Listeria monocytogenes

Abstract: The usefulness of risk assessment is limited by its ability or inability to model and evaluate risk uncertainty and variability separately. A key factor of variability and uncertainty in microbial risk assessment could be growth variability between strains and growth model parameter uncertainty. In this paper, we propose a Bayesian procedure for growth parameter estimation which makes it possible to separate these two components by means of hyperparameters. This model incorporates in a single step the logistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(62 citation statements)
references
References 56 publications
2
60
0
Order By: Relevance
“…The dispersion was sometimes consistent with the biological variability obtained by other authors. Thus, Pouillot et al (2003) observed a mean SD of 1AE26°C for the biological variability of T min against an SD of 2AE55°C in our study. For the optimal specific growth rate of L. monocytogenes in milk, they observed a mean SD of 0AE18 h…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The dispersion was sometimes consistent with the biological variability obtained by other authors. Thus, Pouillot et al (2003) observed a mean SD of 1AE26°C for the biological variability of T min against an SD of 2AE55°C in our study. For the optimal specific growth rate of L. monocytogenes in milk, they observed a mean SD of 0AE18 h…”
Section: Discussionsupporting
confidence: 57%
“…To define confidence limits for predictions and to overpass the difficulties linked to the use of the classical bias and accuracy factors, we used the model parameter estimations distributions to estimate lower and upper confidence limits for the predicted growth rates. We assumed that the minimal cardinal values and the MICs were normally distributed and that the optimal specific growth rates followed a gamma distribution (Pouillot et al 2003). The distribution expectations were set to the mean of the observed values (Table 3), that was )1AE72°C for T min , 4AE26 for pH min HCl, 4AE71 for pH min lactic acid, 0AE913 for a w min , 25AE0 lmol l )1 for MIC nit , 31AE9 ppm for MIC phe , and 3AE04 for MIC CO 2 The distribution SDs were set according to the variability of the parameter estimations observed.…”
Section: Performance Characterization Of the Selected Modelsmentioning
confidence: 99%
“…In order to take into account the strain variability in the latter model, a normal distribution N(Ϫ2.47, 1.26) was used for T min , as proposed by Pouillot et al (43). The lag time at a certain temperature was calculated based on the physiological state parameter h 0 .…”
Section: Methodsmentioning
confidence: 99%
“…In these models, hyperprior distributions are assigned to hyperparameters. Through the hyperprior distributions, hierarchical Bayesian models account for the variability and the uncertainty of the parameters of interest (23,58,61).The two statistical methods were applied to the estimation of the contamination of vegetables with the food-borne pathogenic bacterium Listeria monocytogenes. L. monocytogenes has caused several recognized outbreaks of food-borne infections in which vegetables were implicated; it is regularly isolated from fresh vegetables and can survive and grow even at low temperatures (7,8,34,54,65).…”
mentioning
confidence: 99%
“…In these models, hyperprior distributions are assigned to hyperparameters. Through the hyperprior distributions, hierarchical Bayesian models account for the variability and the uncertainty of the parameters of interest (23,58,61).…”
mentioning
confidence: 99%